“procesamiento de la acerola ( Malpighia punicifolia): Elaboración de mermelada” - Hidalgo Ríos, Caroly Margarita (2003)
The Acerola or Cerezo (Malpighia punicifolia ), is a fruit that is G.ultivated with a great deal of facility in our Region, these fruits are harvested 3 or 4 times to the year. The characteristic organolépticas that possesses, as color, flavor and fragrance are quite pleasant, besides possesses nutritious qualities as Carbohidratos, Mineral, Fiber, Vitamins; standing out the presence of Vitamin C, whose content is over the content of the fruits cítricas very appreciated by being considered rich in the content of this vitamin. The physical performance average of the fruit is of 60.3% pulpa and shell, 6.3% pedúnculo, 33.4% seed. The purpose o:fthe Present I Work of Investigation went to determine the most adequate Parameters of Prosecution for the Elaboration ofMermelada of Acerola and to carry out the trials of storage to determine the stability of the product obtained. Do it devised an Experimental Design, continuing the traditional flow of mermeladas, the which had greater emphasis to determine the best formulation of the ingredients, being traveled through to 3 relations of Pulpa: Sugar (45:55, 50:50 and 60:65), submitted each one ofthem with addition of acid cítrico to 3 levels ofpH (2.9, 3.2 and 3.4), of where their obtained 9 processing, the which they devised bein established for the time of cocción 30 minutes. A:fter the elaboration the mermeladas Were EvaJuated Sensory according to the Test Not Paramétrica ofDurwin, by means of a scale hedónica where themselves. Qualified the color, consistency and f1avor. It processed the information was obtained that the best combination corresponded to the relation 50:50 to a pH of 3.2. The flow of operations recommended for the elaboration of mermelada of acerola is: Selection-Classification, Washed, despulpado-sifting, Formulation, Cocción, Concentration, Pre-Cooling OFF, Bottled, Chi11ed and Storage. To determine the stability of the product in the storage devised mermelada of acerola according to the best formulation, the which was stored to temperature environment (27 ºC) by a period of 60 days. The evaluations physical-chemistry, they were carried out to the 1, 15, 30, 45 and 60 days, the which show good stability of the product. The analyses microbiológicos were carried out to the start and to the end of the storage, being obtained negative results, as product of the asepcia during the prosecution and the correct one bottled of the products. The sensory evaluation was carried out to · the end of the storage, being verified the acceptance of the mermelada of acerola set against other similar commercial products.